FAIR for whom? Commentary on Hofmann et al. (2021) - M, Stefan (Empirical Musicology Review, 2021)
In this commentary on Hofmann et al. (2021), the notion of ethnomusicology and some of its underlying biases are questioned and reflected in the light of applying FAIR data principles to musicological research data from outside a Western canon and its musical practices.